Saponification Using Extracted Oil From Elettariopsis Curtisii And Brucea Amarissima - Aisyah Qaisarah Amir Hamzah; Faqehah Aishah Mohamad Fakhzan; Muhammad Faris Zafran Mohd Farahan; Liyana Amalina Adnan; Nurdalila A’wani Abdul Aziz; Nur Fazidah Asmuje@Asmuzi; Hakimi Shaffie (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025